2020
DOI: 10.1186/s13287-020-02026-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-218 affects hypertrophic differentiation of human mesenchymal stromal cells during chondrogenesis via targeting RUNX2, MEF2C, and COL10A1

Abstract: Background Human mesenchymal stromal cells (MSC) hold hopes for cartilage regenerative therapy due to their chondrogenic differentiation potential. However, undesirable occurrence of calcification after ectopic transplantation, known as hypertrophic degeneration, remains the major obstacle limiting application of MSC in cartilage tissue regeneration approaches. There is growing evidence that microRNAs (miRs) play essential roles in post-transcriptional regulation of hypertrophic differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…In our previous studies using microRNA microarray analyses with application of 1349 miR probes, we identified top 15 differentially expressed miRs that reached over 60-fold changes between MSC that underwent hypertrophic differentiation versus AC that retained the stable mature chondrocyte phenotype during an in vitro chondrogenesis time-course in 3D pellet cultures (Gabler et al, 2015;Melnik et al, 2020). The most striking differential expression profiles were observed for the miR-181 family that also correlated with the progression of the successive maturation stages of chondrogenesis.…”
Section: Differential Expression Of Mir-181a Between Mesenchymal Stromal Cells and Articular Chondrocytes During Differentiation Correlatmentioning
confidence: 98%
See 4 more Smart Citations
“…In our previous studies using microRNA microarray analyses with application of 1349 miR probes, we identified top 15 differentially expressed miRs that reached over 60-fold changes between MSC that underwent hypertrophic differentiation versus AC that retained the stable mature chondrocyte phenotype during an in vitro chondrogenesis time-course in 3D pellet cultures (Gabler et al, 2015;Melnik et al, 2020). The most striking differential expression profiles were observed for the miR-181 family that also correlated with the progression of the successive maturation stages of chondrogenesis.…”
Section: Differential Expression Of Mir-181a Between Mesenchymal Stromal Cells and Articular Chondrocytes During Differentiation Correlatmentioning
confidence: 98%
“…Expression levels of mRNA and miR were calculated using 2-CT method (Rao et al, 2013) and normalized to housekeeping genes Actin Beta (ACTB), Hypoxanthine-guanine phosphoribosyltransferase (HPRT), Ribosomal Protein L13 (RPL13), and Cleavage and Polyadenylation Specific Factor 6 (CPSF6) (for mRNA), or U6 (Small Nuclear Ribonucleoprotein U6, SNRNU6) (for miR). All primers used for the assay were listed before (Melnik et al, 2020). For monitoring expression of human RSPO2 (NM_178565.4) the following primers were used: forward 5 TGTCCAACCATTGCTGAATC3 and reverse 5 TCCTCTTCTCCTTCGCCTTT3 , and human KLF15 1 http://www.targetscan.org/vert_72/ 2 http://mirwalk.umm.uni-heidelberg.de/ 3 https://bioweb.pasteur.fr/packages/pack@miRanda@3.3a 4 https://tools4mirs.org/software/mirna_databases/micrornaorg/ (NM_014079) was measured using forward 5 AGCCGCAG AACTCATCAAAA3 and reverse TTGATGTGCTTGGAGA GGTG.…”
Section: Rna Extraction Quantitative Reverse-transcriptase Pcrmentioning
confidence: 99%
See 3 more Smart Citations